The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1098/rspb.2003.2389
|View full text |Cite
|
Sign up to set email alerts
|

The energetic budget ofAnopheles stephensiinfected withPlasmodium chabaudi: is energy depletion a mechanism for virulence?

Abstract: Evidence continues to accumulate showing that the malaria parasites (Plasmodium spp.) reduce the survival and fecundity of their mosquito vectors (Anopheles spp.). Our ability to identify the possible epidemiological and evolutionary consequences of these parasite-induced fitness reductions has been hampered by a poor understanding of the physiological basis of these shifts. Here, we explore whether the reductions in fecundity and longevity are the result of a parasite-mediated depletion or reallocation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…The authors conclude by calling for more studies to investigate the physiological role of glucose in the Plasmodium-mosquito interaction. Taken together with our results, these experiments suggest the possibility that prior to becoming infective to the vertebrate host during immature infection, Plasmodium manipulates the sugar uptake of the vector [43] and then, once reaching the infective stage, manipulates the vector's behaviour through altered normal neuronal functions, by inducing in the head increased glucose oxidation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The authors conclude by calling for more studies to investigate the physiological role of glucose in the Plasmodium-mosquito interaction. Taken together with our results, these experiments suggest the possibility that prior to becoming infective to the vertebrate host during immature infection, Plasmodium manipulates the sugar uptake of the vector [43] and then, once reaching the infective stage, manipulates the vector's behaviour through altered normal neuronal functions, by inducing in the head increased glucose oxidation.…”
Section: Discussionsupporting
confidence: 77%
“…A recent study of the energetic budget of A. stephensi infected with P. chabaudi [43] revealed that the body of mosquitoes infected with the oocyst stage contained up to 50% more glucose than control mosquitoes. The authors demonstrated that this phenomenon is parasite-mediated and results from increased glucose uptake from blood and not from a reallocation of resources.…”
Section: Discussionmentioning
confidence: 99%
“…However, both human history and agricultural experience suggest that another type of interaction may also be critical: that between hosts and their parasites (e.g., Brown 2003;Cory and Myers 2004;Fitze et al 2004). For example, recent studies on a diverse array of taxa confirm that parasite infestation can modify the host's physiology (Kelly et al 2003;Rivero and Ferguson 2003;Simon et al 2004), behaviour (Dezfuli et al 2003;Field et al 2003;Fitze et al 2004;Vala et al 2004), developmental trajectories (Bize et al 2003), ecology (Snoeijs et al 2004), life-history schedules (Guinnee et al 2003;Neuhaus 2003;Fargallo and Merino 2004;Guinnee and Moore 2004;Madsen et al 2005), and reproductive success (Hurd and Ardin 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because saliva of mosquitoes contain parasite (Plasmodium) that causes malaria (Rivero et al, 2003). The sporozoites that present in the saliva of mosquito can manipulate the behaviour of their insect vector by increasing the biting rate (Schwartz and Koella, 2001).…”
Section: Discussionmentioning
confidence: 99%